2013
DOI: 10.1007/s10995-013-1297-7
|View full text |Cite
|
Sign up to set email alerts
|

Views of Women and Clinicians on Postpartum Preparation and Recovery

Abstract: To explore important domains of women’s postpartum experiences as perceived by postpartum mothers and obstetricians/midwives, and to investigate how postpartum care could enhance patient preparation for the postpartum period. Qualitative research study was conducted to explore women’s and clinicians’ perceptions of the postpartum experience. Four focus groups of postpartum women (n = 45) and two focus groups of obstetric clinicians (n = 13) were held at a large urban teaching hospital in New York City. All foc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
98
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(111 citation statements)
references
References 27 publications
4
98
0
2
Order By: Relevance
“…The current system provides frequent maternal care prenatally, but less so to the new dyad postnatally when breastfeeding support may be essential. Our study confirmed and built on the findings of Martin et al 8 that the postpartum gap in care is problematic and that few HPs are providing care or know what care is provided during this time. Also consistent with prior research, 9 there was general consensus among our participants that better prenatal breastfeeding care is needed to prepare women before labor and delivery.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…The current system provides frequent maternal care prenatally, but less so to the new dyad postnatally when breastfeeding support may be essential. Our study confirmed and built on the findings of Martin et al 8 that the postpartum gap in care is problematic and that few HPs are providing care or know what care is provided during this time. Also consistent with prior research, 9 there was general consensus among our participants that better prenatal breastfeeding care is needed to prepare women before labor and delivery.…”
Section: Discussionsupporting
confidence: 87%
“…8,30,31 In our study, physicians noted that time providing breastfeeding care may not be reimbursable, which may be an important barrier, particularly for those who care for a high proportion of women of low socioeconomic status and work in busy clinics. Furthermore, one physician reported that he primarily provides breastfeeding care for his private patients.…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…Empirical literature has consistently demonstrated that poor relationships with husbands or family members (i.e., relationships with mothers and/or mothers-in-law) are linked to a greater likelihood of women experiencing postpartum depressive symptoms post-delivery (Leung et al, 2005; Saligheh et al, 2014; Martini et al, 2015). Furthermore, studies have shown that a lack of psychological preparedness for pregnancy and insecure attachment styles to partners (i.e., avoidance and anxiety) are associated with a higher risk of postpartum depression (Sabuncuoǧlu and Berkem, 2006; Martin et al, 2014). Moreover, there is a preference for giving birth to a boy in some Asian societies, and the association between infant’s sex and postpartum depression has attracted scholars’ interest.…”
Section: Introductionmentioning
confidence: 99%
“…Determining the effectiveness of antenatal education in promoting breastfeeding duration and exclusivity is important as many new mothers report that they are largely unprepared for their early breastfeeding experiences. [22][23][24][25] Furthermore, even among mothers intending to exclusively breastfeed, newborns are frequently supplemented with infant formula early in the postnatal period, and supplements have a substantial negative effect on breastfeeding duration. [26][27][28] Thus, antenatal breastfeeding education, if effective, offers an opportunity to intervene early, increase rates of exclusive breastfeeding, and extend overall breastfeeding duration.…”
mentioning
confidence: 99%